OS12.4.A MHC class II-restricted transgenic T cell receptor therapy targeting mutant capicua transcriptional repressor in experimental gliomas. (9th September 2021) - Kilian, M; Friedrich, M; Sanghvi, K; Green, E; Pusch, S; von Deimling, A; Wick, W; Sahm, F; Platten, M; Bunse, L
Abstract: BACKGROUND: Glioma subtypes are classified according to their characteristic mutations and show a high degree of resistance to standard therapeutic interventions such as radiotherapy and alkylating chemotherapy. Some of these characteristic mutations have shown to generate immunogenic neoepitopes that can be targeted with immunotherapy. 70% of oligodendrogliomas carry capicua transcriptional repressor (CIC) inactivating mutations. RESULTS: In a screen for potential immunogenic glioma neoepitopes we identified recurrent CIC hotspot mutations at position 215 (CICR215W/Q) expressed in a subset of oligodendrogliomas as an immunogenic major histocompatibility complex (MHC) class II-restricted neoepitopes. Peptide-based vaccination of MHC-humanized mice resulted in the generation of robust mutation-specific T cell responses against CICR215W/Q, restricted to MHC class II. Droplet-based single cell T cell receptor (TCR) sequencing from CICR215W-specific T cell lines enabled retrieval of MHC class II-restricted CICR215W-reactive TCRs. By retroviral transduction of T cells, we established a flow cytometry-based testing platform of retrieved TCRs and were able to show the top reactive TCR against CICR215W to be shared between individual mice. Using a newly developed glioma model in MHC-humanized mice induced by CRISPR-based delivery of tumor suppressor targeting guide RNAs, we show that adoptive intraventricular transfer of CICR215W-specific TCR-transgenic T cells exert anti-tumor responses against CICR215W-expressing syngeneic gliomas. CONCLUSION: The integration of immunocompetent MHC-humanized orthotopic glioma models in the discovery of shared immunogenic glioma neoepitopes facilitates the identification and preclinical testing of HLA-restricted neoepitope-specific TCRs for locoregional TCR-transgenic T cell adoptive therapy.